Japanese disaster nursing readiness evaluation index: Turkish adaptation validity and reliability study - Azizoğlu, Hatice; Korkmaz, Evin; Hacıdursunoğlu Erbaş, Dilay; İlbey Koç, Betül and Eti Aslan, Fatma (The European Research Journal, 2025)
Objective: Disaster is a global problem all over the world, and it is essential to measure the readiness of nurses, who play a major role in disaster response, with a valid and reliable tool. This study was conducted to adapt the Japanese Disaster Nursing Readiness Evaluation Index into Turkish and to analyze its validity and reliability. Methods: A total of 202 nurses were reached in this methodological study. The reliability parameters of the scale were examined with Cronbach Alpha and split-half. In addition, Confirmatory Factor Analysis was performed for the construct validity of the scale and 27% sub-item analysis was performed for item discrimination. Results: According to Confirmatory Factor Analysis, the structural equation model, indicating its associated with 31 items and the six-factor structure of the scale. The factor loading values of all items were between 0.450 and 0.920. The alpha values obtained from the subscsles of the scala ranged between 0.771 and 0.883, and the overall alpha value was calculated as 0.905. Conclusions: Based on the findings of the study, it was concluded that the Japanese Disaster Nursing Preparedness Assessment Index is valid and reliable for the Turkish society.